DOES SUSTAINABILITY DISCLOSURE HAVE A MODERATING ROLE IN EXAMINING FIRM VALUE IN BANKING INDUSTRY? - Hapsari, Diah Oktavia; Firmansyah, Amrie (Kesatuan Press, 2024)
This study seeks to experimentally assess the impact of financial performance on the firm value of the banking subsector and examine sustainability disclosure as a moderating variable. The study focused on banking subsector companies listed on the IDX in 2020-2022. Multiple linear regression was used to test cross-sectional data processed with Eviews 12. The test results demonstrate that profitability has a considerable beneficial impact on firm value. Meanwhile, leverage minimizes firm value because the primary banking business process involves consumer loans and receivables. Therefore, investors pay little attention to company debt. Sustainability disclosure cannot balance the relationship between financial success and firm value. The sustainability disclosures need to meet investors' expectations. Stakeholders may have differing perspectives on the relevance and influence of sustainability data on profitability and firm value.